2012
DOI: 10.7150/ijms.4722
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Honey and Propolis toward Drug Multi-Resistant Staphylococcus Aureus, Escherichia Coli and Candida Albicans Isolates in Single and Polymicrobial Cultures

Abstract: Background: Propolis and honey are natural bee products with wide range of biological and medicinal properties. The study investigated antimicrobial activity of ethyl alcohol extraction of propolis collected from Saudi Arabia (EEPS) and from Egypt (EEPE), and their synergistic effect when used with honey. Single and polymicrobial cultures of antibiotic resistant human pathogens were tested.Material and methods; Staphylococcus aureus (S. aureus),), Escherichia coli (E. coli) and Candida albicans (C.albicans) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 50 publications
4
107
0
11
Order By: Relevance
“…According to the research conducted by Waili et al [29] on the synergistic efects of propolis extracts with ethyl alcohol on S. aureus and our studies agree that potentiates the efect of propolis another drug on S. aureus isolates; with the diference that Waili used as a second active substance honey; and this work highlighted the efects of propolis in combination with extracts of oregano.…”
Section: Oregano-propolis Combinationsupporting
confidence: 87%
“…According to the research conducted by Waili et al [29] on the synergistic efects of propolis extracts with ethyl alcohol on S. aureus and our studies agree that potentiates the efect of propolis another drug on S. aureus isolates; with the diference that Waili used as a second active substance honey; and this work highlighted the efects of propolis in combination with extracts of oregano.…”
Section: Oregano-propolis Combinationsupporting
confidence: 87%
“…Some of 39 South Africa propolis samples exhibited much higher antistaphylococcal activity in comparison to three tested samples of Brazilian propolis with MIC and MBC values of only 6 μg/mL [51]. Al-Waili and coworkers revealed that ethanolic extracts of propolis collected from Saudi Arabia (EEPS) and from Egypt (EEPE) efectively inhibited the growth of antibiotic resistant E. coli, S. aureus and C. albicans in single and polymicrobial cultures [52]. Strong antioxidant and antibacterial activity of propolis sourced from three diferent areas of Sonoran Desert in northwestern Mexico were conirmed in the research of Velazquez group [53].…”
Section: Bee Products and Essential Oils As Alternative Agents For Trmentioning
confidence: 99%
“…The antimicrobial activity of the combination of RJ and honey was studied [37,38], and the additive activity of RJ and honey against P. aeruginosa was found, as comparison with the experiments in this study, where the water soluble F-RJ (M) did not affect the Forest honey in term of statistically stronger antimicrobial activity. Al-Waili et al [39] also analysed the antimicrobial activity of the combination of ethanol extract of propolis and honey from Saudi Arabia, and found the synergism between the ethanol extract of Saudi propolis or Egyptian propolis with honey from Saudi Arabia in term of killing of MRSA, E. coli and C. albicans. These data are comparable with this study, despite the WSP Greit120 was used in combination with Forest honey.…”
Section: The Growth Promoting Activity Of Tlt Cell Line By the Combinmentioning
confidence: 99%